Estimation of Water Defficit in Wheat Using Micrometeorological and Soil Moisture Variables - Painuli, D K; Ghildyal, B P (Annals of Arid Zone, 2016)
Water deficit in four wheat (Triticum aestivum L.) cultivars (HD 1982, HD 2009, UP 319, and Kalyan Sona) was estimated using micrometeorological (temperature, relative humidity, wind speed, and solar radiation) and soil moisture data. Water deficit could be estimated accurately (R2 between 0.951 and 0.997) when the differences between cultivars and effect of crop age were assumed significant. But the accuracy decreased when the difference between cultivars only was assumed significant (R2 0.690 and 0. 849). Accuracy decreased further (R2 0.264) when the differences between cultivars and effect of crop age were assumed negligible.